Effectiveness of pyroligneous acid pyrolysed from tropical lignocellulosic biomass as biopreservative - Lee, Soon Heng (2015)
Lignocellulosic biomass are natural and abundantly available resource has been steadily gaining attention from relevant industries as feedstock for the production of chemicals, fuels and biocompatible materials due to increased concern in economic and environmental issues. The potential of being converted into usable chemicals which pyroligneous acids is one of the chemicals from the distillation of smoke generated during charcoal making. It was found to be potential use as bio-preservative due to the complex mixture of water, acetic acid, methanol, acetone, formic acid, guaiacols,catecols, syringols, vanillins, furan carboxaldehydes, isoeugenol, pyrone and more than 200 organic compounds including phenolic compounds, which are pyrolytic products of lignin and hemicellulose. This study focuses on development of pyroligneous acid as bio-preservative against wood biodegradable agents. Pyroligneous acids derived from different types of lignocellulosic biomass at temperature of; 300°C,400°C and 500°C. The chemical compounds were then analysed using Fourier Transform Infrared (FT-IR) Spectroscopy and Gas chromatography – mass spectrometry (GC-MS). The results showed that pyroligneous acids derived with 3 temperature ranges were slightly different in chemical compositions, but significantly different in the contents of each chemical component. A total 24, 23 and 22 compounds were identified from the Rubberwood, OPT and Mix Hardwood pyroligneous acid,respectively. Ketones, organic acids, aldehydes, esters, phenols and its derivatives were found in the pyroligeneous acids where acetic acid and phenol were the primary compounds in the pyroligneous acids. For the efficacy of pyroligneous acid test,rubberwood test block was immersed in pyroligneous acid for 24 h at room temperature. Treated rubberwood test block were later tested against mold (Penicillium chrysogenum), white rot fungus (Pycnoporous sanguineus) and subterranean termites (Coptotermes curvignathus) according to ASTM standard methods. Results showed that Pyroligneous acids pyrolysed from sawdust of rubberwood, oil palm trunk and mixed hardwood are effective against biodegradable agents. The test blocks treated with all pyroligneous acids produced from different temperatures are equally effective against the mold, decay fungi and termites. Compounds 2-methoxy-phenol and 4-ethyl-2-methoxy-phenol contributed to inhibit Penicillium chrysogenum, compounds 4-ethyl-2-methoxy-phenol contributed to inhibit Pycnoporus sanguineus while compounds acetic acid and phenol in pyroligneous acids found to be active chemicals in controlling termite attacks. Therefore, further studied had been carry out using OPT and Rubberwood pyroligneous acid pyrolysed at 500°C with impregnation method using different concentration of 100%, 50% and 30% of pyroligneous acid. Results showed that dilution of pyroligneous acid were effective against mold and decay fungi while only had mild effectiveness against termites. Rubberwood and OPT pyroligneous acids at 500oC in dip-treatment process gave the best antimicrobial properties while Mix hardwood showed the best performance in antitermites properties. All the pyroligneous acid used in dip-treatment process showed equal antifungal properties. Concentration 50% Rubberwood and 30% OPT pyroligneous acids were effective against mold inhibition and decay fungi with impregnation process compared to 100% concentration pyroligneous acids with diptreatment process. However, concentration of pyroligneous acids in impregnation and dip-treatment process showed mild effective to termites attacked.